2020
DOI: 10.3390/life10070116
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Adenine Enhance Osteogenesis in the Osteoblast-Like MG-63 Cells

Abstract: Background: Adenine is a purine with a role in cellular respiration and protein synthesis. It is considered for its pharmacological potential. We investigated whether anti-inflammatory effect of adenine benefits on the proliferation and maturation of osteoblastic cells. Methods: Human osteoblast-like cells (MG-63) were cultured with adenine under control conditions or pre-treated with 10ng/mL of tumor necrosis factor-α (TNF-α) followed by adenine treatment. Cell viability was examined using dimethylthiazol dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The DNA hydrogel was able to promote new bone formation, even though it degraded relatively early on (as judged by the in vitro experiments). This supports the hypothesis that DNA exerts a rather early osteogenic inductive effect, which can potentially be heightened as DNA degrades and releases extracellular phosphate ions from its phosphate-rich backbone and likely adenine, which have been shown to induce migration and up-regulate osteogenic differentiation ( 21 28 ). The ratio of bone volume to tissue volume (BV/TV) in the region of interest was measured for each sample to characterize the amount of trabecular bone formed in the calvarial defect.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The DNA hydrogel was able to promote new bone formation, even though it degraded relatively early on (as judged by the in vitro experiments). This supports the hypothesis that DNA exerts a rather early osteogenic inductive effect, which can potentially be heightened as DNA degrades and releases extracellular phosphate ions from its phosphate-rich backbone and likely adenine, which have been shown to induce migration and up-regulate osteogenic differentiation ( 21 28 ). The ratio of bone volume to tissue volume (BV/TV) in the region of interest was measured for each sample to characterize the amount of trabecular bone formed in the calvarial defect.…”
Section: Resultssupporting
confidence: 80%
“…This value corresponds to a concentration of 3.1 mM of adenine in the culture medium. Previously, it was reported that adenine up-regulates osteogenic genes using exogenous adenine supplementation of 100 µM for 24 h ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immature osteoblasts produce many specific proteins, including alkaline phosphatase, collagen type I, osteopontin and bone sialoprotein and so block their potential to differentiate into the chondrocytic and adipocytic lineage [ 31 , 35 ].…”
Section: Osteogenic Differentiation and Its Testingmentioning
confidence: 99%
“…ALP is a membrane-bound enzyme expressed in immature osteoblast cells. It is considered to be a marker for their early differentiation and plays a key role in the calcification of bones [ 35 ]. ALP hydrolyzes pyrophosphate and supplies inorganic phosphate to enhance mineralization as well as to reduce extracellular pyrophosphate, an inhibitor of mineral formation [ 36 ].…”
Section: Osteogenic Differentiation and Its Testingmentioning
confidence: 99%